2005
DOI: 10.1111/j.1464-410x.2005.05688.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tamsulosin and naftopidil for efficacy and safety in the treatment of benign prostatic hyperplasia: a randomized controlled trial

Abstract: OBJECTIVES To compare the efficacy and safety of two α1a/α1d adrenoceptor (AR) antagonists with different affinity for the α1AR subtypes, tamsulosin and naftopidil, in the treatment of benign prostatic hyperplasia (BPH). PATIENTS AND METHODS Patients with BPH were randomized to receive either tamsulosin or naftopidil. The primary efficacy variables were the changes in the total International Prostate Symptom Score (IPSS), maximum flow rate on free uroflowmetry, and residual urine volume. The secondary efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 27 publications
5
102
0
1
Order By: Relevance
“…Among these, it is important to emphasize the occurrence of progressive changes in the urinary bladder with aging, which take place at the same time as histopathological alterations of the prostate that may contribute to the LUTS [1,2]. These aspects reinforce the previous experiences that show the absence of a direct relationship between the prostate gland volume and the degree of urinary obstruction called ''prostatism sans prostate '' or ''small prostate, big residual'' [10,[23][24][25][26][27]. Explanations for this absence of correlation implied the occurrence of an intrinsic prostate tension, based on the contraction of stromal smooth muscles or extrinsic tension of the capsule on the transitional hypersplastic tissue [23][24][25].…”
Section: Discussionmentioning
confidence: 73%
“…Among these, it is important to emphasize the occurrence of progressive changes in the urinary bladder with aging, which take place at the same time as histopathological alterations of the prostate that may contribute to the LUTS [1,2]. These aspects reinforce the previous experiences that show the absence of a direct relationship between the prostate gland volume and the degree of urinary obstruction called ''prostatism sans prostate '' or ''small prostate, big residual'' [10,[23][24][25][26][27]. Explanations for this absence of correlation implied the occurrence of an intrinsic prostate tension, based on the contraction of stromal smooth muscles or extrinsic tension of the capsule on the transitional hypersplastic tissue [23][24][25].…”
Section: Discussionmentioning
confidence: 73%
“…In the present study, the improvements in the IPSS and QOL index were significantly higher with 0.2 mg tamsulosin than with 50 mg naftopidil. Gotoh et al [15] have reported the results of a prospective randomized study comparing the difference in clinical efficacy between 50 mg naftopidil and 0.2 mg tamsulosin for 12 weeks. They found no significant difference in the change of the IPSS between the 2 drugs (p = 0.060).…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference (which was suggested to depend on differences in affinity for a 1 -AR subtypes between the drugs) could not be reproduced in a randomized head-to-head comparison between the drugs. 41 Based on available evidence, the importance of the a 1D -ARs on the detrusor myocytes for LUTS generation cannot be established. Nor can it be excluded that a 1D -ARs located elsewhere in the bladder, for example, the vasculature, 42 or in other structures, are of importance.…”
Section: Subtype Selective a A 1 -Ar Antagonistsmentioning
confidence: 99%